Examples of fractional replications (1/2)4³ e (1/4)44 for fitting quadratic polinomial models - Andrade, Dalton F. de; Noleto, Antonio Q. (Pesquisa Agropecuaria Brasileira, 2014)
In this work two examples of fractional replications (1/2)43 e (1/4)44 are presented, which allow the coefficients of the linear, quadratic and linear x linear interaction effects to be independently estimated from each other, whenever a quadratic polynomial model is used to present the response surface. It is also shown how these factorial schemes can be used in block designs so that the effects of interest be not confounded with block effects.